Frontispiece: Three‐Component Domino Knoevenagel/Vinylogous Michael Reaction: Entry to Challenging o‐Terphenyls. Issue 25 (27th April 2018) - Grau, Dominik; Grau, Benedikt W.; Hampel, Frank; Tsogoeva, Svetlana B.
Abstract : Combination of a novel organocatalytic three‐component two‐step domino reaction with a subsequent new three‐step domino process, starting from easily accessible nitroolefins, malononitrile, and arylacetaldehydes, allows an unprecedented easy access to challenging highly functionalized o ‐terphenyls, which are of high interest for materials science and medicinal chemistry. For more information, see the Full Paper by S. B. Tsogoeva and co‐workers onpage 6551 ff.